Assessment of clinical diagnostic accuracy compared with pathological diagnosis of basal cell carcinoma - Ebrahimzadeh-Ardakani Mohammad; Moghimi Mansour; Kafaie Parichehr; Dehghani Farideh; Rashidi Amirhossein; Shojaoddiny-Ardekani Ahmad (Wolters Kluwer Medknow Publications, 2015)
Background: Basal cell carcinoma (BCC) is the most common type of skin cancer, afflicting light skin more than dark skin people. This malignancy metastasizes rarely and has unique histological properties. Aims and Objectives: We focused on the accuracy of clinical diagnoses of BCC by specialists. Materials and Methods: Patients' information for 4-year period between 2007 and 2011 was extracted from files at a Pathology Department. The results were analyzed using the Chi-square method and SPSS software. Results: From 367 referred cases dermatologists diagnosed 41% as direct BCC cases, 43.4% through excluding other skin diseases, 4% incorrectly and 1.11% unidentified. For other specialists (including plastic surgeons, ophthalmologists, general surgeons, and general practitioners) these were respectively 47.8%, 22.4%, 6.3% and 23.5%. Dermatologists had diagnosed 107 cases of all skin diseases as BCC through clinical examination of which 78.5% were correctly and 21.5% incorrectly diagnosed. The same parameters for all other specialists were respectively 77.36% and 22.64%. Diagnostic sensitivity, positive reportability, clinical conjecture indicator (CCI) and clinical diagnostic indicator were respectively 84.4%, 78.5%, 121.5% and 75.6%; whereas for other specialists these indicators were 70 among cases diagnosed by dermatologists as BCC, where pathological results showed other causes. The most common diagnosis by pathologists and other specialists was reported as squamous cell carcinoma (SCC). Among cases not diagnosed by dermatologists as BCC, where pathological results indicated BCC, the most common clinical diagnosis was malignant melanoma by dermatologists and SCC by other specialists. Conclusion: Dermatologists diagnosed BCC with higher sensitivity and positive reportability; also, CCIs and clinical diagnostic correctness was higher among dermatologists. The necessity for consulting with dermatologists and referring all skin diseases samplings to pathologist is thus clearly visible.